2016
DOI: 10.1038/srep30460
|View full text |Cite
|
Sign up to set email alerts
|

Real time and label free profiling of clinically relevant exosomes

Abstract: Tumor-derived exosomes possess significant clinical relevance due to their unique composition of genetic and protein material that is representative of the parent tumor. Specific isolation as well as identification of proportions of these clinically relevant exosomes (CREs) from biological samples could help to better understand their clinical significance as cancer biomarkers. Herein, we present a simple approach for quantification of the proportion of CREs within the bulk exosome population isolated from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 37 publications
4
119
1
Order By: Relevance
“…74 Lastly, surface plasmon resonance (SPR)-based sensing platforms rely on functionalization of gold surfaces for exosome capture, and therefore also fall into this category. 44,75 …”
Section: Microfluidic-based Exosome Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…74 Lastly, surface plasmon resonance (SPR)-based sensing platforms rely on functionalization of gold surfaces for exosome capture, and therefore also fall into this category. 44,75 …”
Section: Microfluidic-based Exosome Isolationmentioning
confidence: 99%
“…as part of a two-step isolation and detection process. 75 Custom-made SPR chips were employed for analysis of exosomes from breast cancer patient samples, where characteristics of the resulting spectral shifts enabled identification and quantification of exosome populations from serum samples. Electrokinetic methods have also been employed for analysis of exosomal materials, as demonstrated by Akagi et al .…”
Section: Microfluidic-based Exosome Detection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sina et al integrated SPR detection into their two-step isolation and detection strategy [105]. …”
Section: Efforts and Progress Towards Integrated On-a-chip Systems Fomentioning
confidence: 99%
“…[18] Others have been reported to be enriched in certain tumor-associated exosomes, like EGFR and HER2. [19,20] Given that several recent studies have demonstrated enrichment of particular integrins in exosomes derived from a variety of tumor cells, they are interesting potential targets. [2126] …”
Section: Introductionmentioning
confidence: 99%